UK Graduate Education in the Time of COVID-19. (26th January 2022) - Owen, Suzanne
Abstract : The Buzz examines scholarly topics in light of present-day concerns and challenges. This edition centers on the unique challenges of graduate education as a result of the restrictions of COVD-19. In issue 50.1 we heard from scholars working within the context of the US. In this issue, Suzanne Owen of Leeds Trinity University and the Bulletin Advisory Board offers a brief look at the situation in the UK.